The Effect of Maximum Reaction Temperature of Polyurethane Foam on the Effective Thermal Conductivity - Massara Ali Fadhel; Harith H. Al-Moameri; Tawfeeq W. Mohammed (Journal of Engineering and Sustainable Development)
The thermal conductivity of polyurethane foams may be sensitive to many pronounced parameters related to their components and conditions of formation. This study aims to investigate the effect of maximum reaction temperature during forming the foam on the resultant thermal conductivity value. The study used samples from different cases and conditions to monitor the reaction. The cases include standard, with n-pentane or water as blowing agents and ethylene glycol as activation agents. Two conditions have been selected: with and without post-heating. The results have shown that thermal conductivity increases with the increase in the maximum reaction temperature for certain cases (1 g and 2 g). However, for 4 g, there is a decrease in the k-value. In general, the lowest k-value has been noticed for the case of using 1 g of n-pentane (0.033 W/m.K) compared to the reference case that does not use further addition of agents (0.043 W/m.K). The variation of the k-values due to the increasing mass of the agents shows an increment behavior.